Participation in Budget Preparation and Budget Clarity in The Perfomance of Officials Government - latasad, alfira rahmatia r.; Ansar, Muhammad (ADPEBI, 2024)
Participation in budgeting is one way to create a strong financial control system and fulfill related organizational goals by participating in budgeting. The aim of this research is to examine how the performance of government officials in handling regional organization finances is influenced by their involvement in budget formulation and clarity of budget objectives. Data collection was carried out through observation. The sample selection in this study was carried out using purposive sampling, and the sample consisted of 30 Regional Apparatus Organizations (OPD) in Sigi Regency. Multiple linear regression analysis was used in hypothesis testing data analysis using SPSS 25.0. The results of research and testing show that simultaneously budgetary participation and clarity of budget targets have a significant effect on the performance of government officials. Partial participation in budget preparation and clarity of budget targets have a significant effect on the performance of government officials. Keywords: Performance of Government Apparatus, Clarity of Budget Targets, and Performance of Government Apparatus.